(untitled) (European Journal of Pure and Applied Mathematics, 2015)
In this paper, we investigate the structure and properties of duadic, isodual cyclic and formally self-dual codes over the ring R=F_q+vF_q with v^2=v. In addition to the theoretical work on the structure of these codes, we construct examples of good codes over different alphabets from cyclic self-dual and formally self-dual codes over R.